F21 Is bone density altered in early stage huntington's disease patients?—a pilot study. (16th November 2010) - Hughes, A; Price, K; Mason, D; Evans, B; Pettit, R; Evans, W; Rosser, A
Abstract : Background: Huntington's disease (HD) is an autosomal dominant progressive neurodegenerative disorder presenting in midlife. As it is the death of specific neurons within the brain that causes the majority of the disabling symptoms in HD, the research into this disorder has been largely neuron-centred. However, there is a growing body of evidence to suggest that other tissues may be affected by the mutation causing HD. Our previous work demonstrates that the HD gene is expressed in mouse and human bone, and that bone mineral density of 10 month old Q150 mice does not appear to be adversely affected by the mutant form of this gene. Aims: The main objective of this pilot study was to extend the work from the animal model to a human population. Bone density changes were investigated in premanifest and early stage HD patients for this purpose. It was predicted that 80 participants (20 presymptomatic, 20 early symptomatic, 40 controls) would be required to allow a change to be detected at a significance of 5% with a power of 80%. Methods: Bone density and body composition of HD patients, who were either presymptomatic or in the early stages of the disease, were assessed through the use of dual energy x-ray absorptiometry (DXA) scanning and blood collection for bone serum marker analysis. DXA was performed for hip, lumbar spine and whole body. Patients were compared to age-sex matched healthy controls and various confounding factors such as past medical history, drug history, diet and levels of physical activity were taken into account. Results: Preliminary results for 31 participants recruited to date, reveal that male HD patients yield lower scores for lumbar spine and hip bone density compared to controls. Conclusion: Our results suggest that male HD patients may have a reduced bone mineral density when compared with age-matched healthy controls. Further participants are needed before a firm conclusion can be drawn.